Rare data from a lost satellite - Blanton, Elizabeth (Nature (London), 2016)
The Hitomi astronomical satellite observed gas motions in the Perseus galaxy cluster shortly before losing contact with Earth. Its findings are invaluable to studies of cluster physics and cosmology. See Letter p.117 Quiet flows the Perseus cluster The Hitomi collaboration reports X-ray observations of the core of the Perseus cluster of galaxies — the brightest X-ray-emitting cluster in the sky. Such clusters typically consist of tens to thousands of galaxies bound together by gravity and are studied as models of both small-scale cosmology and large-scale astrophysical processes. The data reveal a remarkably quiescent atmosphere, where gas velocities are quite low, with a line-of-sight velocity dispersion of about 164 kilometres per second at a distance of 30–60 kiloparsecs from the central nucleus.